1990
DOI: 10.1007/bf01646858
|View full text |Cite
|
Sign up to set email alerts
|

Ergebnisse einer Doppelblindprüfung Diclofenac+Vitamin B1, B6, B12 versus Diclofenac bei Patienten mit akuten Beschwerden im Lendenwirbelsäulenbereich

Abstract: Several clinical trials have shown that the duration of treatment of painful vertebral syndromes can be shortened by using a combination of vitamins B1, B6, B12 and diclofenac instead of diclofenac. In addition, a more efficient pain relief could be achieved by the combination therapy. In order to confirm these results, we compared the clinical efficacy of diclofenac (25 mg) and a combination preparation with diclofenac (25 mg) plus vitamins B1 (thiamine nitrate 50 mg), B6 (pyridoxine hydrochloride 50 mg) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 2 publications
0
3
0
3
Order By: Relevance
“…Die [7,8,40,41,58], oder die Schmerzen mit einer niedrigeren täglichen Dosis von Diclofenac als normalerweise üblich behandelt werden konnten [40,42].…”
Section: Kombinationen Von B-vitaminen Mit Analgetikaunclassified
“…Die [7,8,40,41,58], oder die Schmerzen mit einer niedrigeren täglichen Dosis von Diclofenac als normalerweise üblich behandelt werden konnten [40,42].…”
Section: Kombinationen Von B-vitaminen Mit Analgetikaunclassified
“…The combination of diclofenac with vitamins B 1 , B 6 , and B 12 has been reported to be beneficial in the treatment of painful conditions, including post-operative pain [9], osteoarthritis [10], and especially low back pain. Prior to the publication of the DOLOR trial, encouraging results in clinical studies of low back pain employing the combination of vitamins B 1 , B 6 , and B 12 with diclofenac had been reported in the literature, especially in terms of shortened treatment time to satisfactory analgesia when compared with diclofenac monotherapy [11]- [14]. The results of the DOLOR study confirmed these findings and the results of this post-hoc analysis reinforced the benefit of adding vitamins B 1 , B 6 , and B 12 to diclofenac therapy in terms of shorter treatment time to desired clinical effect.…”
Section: Discussionmentioning
confidence: 99%
“…The methodological aspect is highlighted by a report [16,17] that the consumption of 100 g fat after a 12 hours fasting period causes a significant decrease (!!) in platelet aggregability upon both, ADP and collagen.…”
Section: Discussionmentioning
confidence: 99%